High‐Performance, Solution‐Processed Non‐polymeric Organic Photodiodes. Issue 1 (29th September 2014) - Kim, Il Ku; Pal, Bhola N.; Ullah, Mujeeb; Burn, Paul L.; Lo, Shih‐Chun; Meredith, Paul; Namdas, Ebinazar B.
<x xml:space="preserve">Abstract</x> High‐performance, solution‐processed, non‐polymeric broadband organic photodiodes (OPDs) with a dark current density of 0.11 nA cm‐2, responsivity of 0.4 A W‐1, and detectivity of up to 9.2 × 1012 Jones are demonstrated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>